1975
DOI: 10.1136/bmj.2.5963.112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of truncal, selective, and highly selective vagotomy on glucose tolerance and insulin secretion in patients with duodenal ulcer. Part I-Effect of vagotomy on response to oral glucose.

Abstract: SummaryAn oral glucose tolerance test was performed in patients who had undergone truncal vagotomy and pyloroplasty, bilateral selective vagotomy and pyloroplasty, or highly selective vagotomy without a drainage procedure at least six months earlier. The results were compared with those from patients with chronic duodenal ulcer before operation. In all three groups of patients after vagotomy more rapid rates of rise of blood glucose and higher peak concentrations were observed than in patients who were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1976
1976
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…While in this short-term study in rats after TV plus an adequate drainage operation we find no changes in weight gain, glucose and insulin, others have observed altered food intake, lower weight gain, higher fasting glucose, lower insulin and lower renal glucose threshold after prolonged observation periods [for details, see Woods and Porte, 1974]. This is in agreement with clinical communications in regard to fast ing glucose and insulin [Humphrey et al, 1975]. The reasons for these dif ferences are unknown, but may relate to differences in surgical and dietary preparation.…”
Section: Discussionsupporting
confidence: 79%
“…While in this short-term study in rats after TV plus an adequate drainage operation we find no changes in weight gain, glucose and insulin, others have observed altered food intake, lower weight gain, higher fasting glucose, lower insulin and lower renal glucose threshold after prolonged observation periods [for details, see Woods and Porte, 1974]. This is in agreement with clinical communications in regard to fast ing glucose and insulin [Humphrey et al, 1975]. The reasons for these dif ferences are unknown, but may relate to differences in surgical and dietary preparation.…”
Section: Discussionsupporting
confidence: 79%
“…The present study and the observation that the enteral insulin stimulation is well preserved in man after truncal vagotomy [21] suggest that the incretin effect probably is of humoral nature. The results concerning the enteral insulin stimulation in man are however, contradictory, in as much as Humphrey et al [22] recently found, that truncal vagotomy led to a diminished insulin response to oral glucose, whereas the insulin response to intravenously administered glucose was unchanged.…”
Section: Discussionmentioning
confidence: 90%
“…This regula tion seems to be impaired possibly due to vagotomy seen after TG [8][9][10][11][12][13][14][15], Galactose does not stimulate insulin se cretion [17]. Thus the blood galactose con centration in galactose test is determined by intestinal adsorption and liver elimination rates.…”
Section: Discussionmentioning
confidence: 99%
“…Vagotomy and 'chemical vagotomy' by atropine may impair the insu lin response to glucose [8][9][10][11][12], The patients after total gastrectomy may have a relative lack of insulin during postprandial hypergly cemia [ 13], and as a sign of long-term hyper glycemia elevated HbAI concentrations have been measured in dumping patients [14]. Results from intraoperative glucagon stimulated C peptide tests 10 min after the midline incision and 60-90 min later after the completion of gastric resection without truncal vagotomy or total gastrectomy with truncal vagotomy suggest that a truncal va gotomy will produce a significant inhibition of insulin secretion [15].…”
Section: Introductionmentioning
confidence: 99%